Kajian Kandungan Logam Berat Merkuri (Hg) dan Timbal (Pb) Pada Beberapa Jenis Kerang di Perairan Pesisir Indonesia - Gery Pratama; Kurnia Andika; Hilfi Pardi (Journal of Research and Education Chemistry, 2024)
Indonesia’s coastal waters have great potential wealth in supporting human life and as an ecosystem for several species. However, this potential is eclipsed by heavy metal pollution caused by industry and domestic activities. The purpose of this study is to determine the concentrations of heavy metals mercury (Hg) and lead (Pb) in numerous species of mussels often found in Indonesian coastal waters. The research method used was systematic literature review. The results showed that coastal waters in several regions I Indonesia, especially in the provinces of Aceh, Central Java, Banten, West Java, East Java and Jakarta, have significant concentrations of heavy metals. Thirteen kinds of mussels were found to have heavy metal pollution. But the most heavily polluted with heavy metals were lead (Pb) and mercury (Hg) were green mussels (Perna viridis). The results demonstrated that many varieties of mussels have higher concentrations of the heavy metals lead (Pb) and mercury (Hg) than the maximum allowed by BPOM Regulation No. 9 of 2022.